Pemetaan dan analisis tingkat kerusakan hutan mangrove di Taman Nasional Kutai berdasarkan data satelit landsat ETM dan kerapatan vegetasi: Mapping and deforestation level of mangrove forest in Kutai National Park base on data satelite image of landsat ETM and vegetation density - Anugrah Aditya Budiarsa; Samsul Rizal (Fakultas Perikanan dan Ilmu Kelautan, Universitas Mulawarman, 2022)
Along with the increase in population in the Kutai National Park (Kutai NP) has raised the land issue of due to the need for living space and the exploitation of natural resources. This study is part of an effort to evaluate the condition of mangrove forests as a first step effort to protect mangrove forests as critical habitat for coastal Kutai NP. The research was conducted in March to April 2012, with the goal of evaluating and measuring vegetation cover and land use (Land use) mangrove forests in coastal Kutai NP. For this purpose, the data is used Landsat ETM + image with 7 bands that recorded in 2008. Process analysis using NDVI (Normalizet Difference Vegetation Index) composite channel by IR (bands 4 and 3), while the extent of the damage was analyzed using standard from Decree of Ministry of environment No. 201, 2004. Base on the research, Kutai National Park has the potential of ± 5192.54 ha of mangroves, mangrove forest ecological conditions in Kutai NP generally be in the grade is still good with vegetation density ranging between 967-1567 ind / ha, Kutai NP In some areas such as the Estuary Sangatta, bay and estuary Sangkima Lombok are areas that have experienced enough land conversion, overall mangrove forest that has been opened by ± 1845.85 ha or 26.2%. Mangrove forests are located close to residential vulnerable to land-use changes.